Material for preparing heat-conducting packaging piece, preparation method of material, heat-conducting packaging piece, preparation method of heat-conducting packaging piece and electronic equipment
By reacting the inorganic thermally conductive material containing silane coupling agent and alkali etched in the presence of water, and then performing a second reaction with the epoxy monomer under the protection of inert gas to form a whole material, the problem of uneven dispersion of inorganic thermally conductive materials is solved and the thermal conductivity of the thermally conductive package is significantly improved.
Patent Information
- Application Number
- CN202510041611.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Inorganic thermally conductive materials in existing thermally conductive packages are unevenly dispersed in the epoxy resin monomer cross-linking network matrix, resulting in limited improvement in thermal conductivity.
The first reaction is performed by a mixing system containing a silane coupling agent, a first organic solvent and an inorganic thermally conductive material after alkali etching in the presence of water to obtain an intermediate, and then the mixing system of the intermediate and epoxy monomer is carried out under the protection of an inert gas to form a whole material connected together by a silane coupling agent.
The uniform distribution of inorganic thermally conductive materials in the epoxy monomer cross-linking network matrix is realized, and a stable thermally conductive network is constructed, which significantly improves the thermally conductive properties of the thermally conductive package.
Smart Images

Figure CN119823408A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermally conductive packaging materials, and more specifically, to a material for preparing a thermally conductive packaging component and a preparation method thereof, a thermally conductive packaging component and a preparation method thereof, and an electronic device. Background Art
[0002] With the rapid development of microelectronic assembly technology and integration technology, the size of logic circuits and electronic devices has been greatly reduced, and electronic devices have become thinner and smaller, while the operating frequency has increased dramatically, resulting in a rapid increase in the heat generated by electronic devices. If the heat cannot be effectively dissipated, the excessive accumulation of heat will increase the temperature of the electronic devices, affecting the normal operation of the electronic devices, and even causing the electronic devices to fail in severe cases. Therefore, electronic devices (especially those using third-generation semiconductors) have higher requirements for the thermal conductivity of the packaging materials they use.
[0003] The packaging material used in electronic devices is generally epoxy resin material. At present, in order to improve the thermal conductivity of the packaging material, the thermal conductive packaging is prepared by "first mixing epoxy resin monomer with inorganic thermal conductive material (including silicon carbide or boron nitride, etc.), and then cross-linking and curing the epoxy resin monomer in the mixed system".
[0004] However, in the above-mentioned method of forming a thermally conductive package, the inorganic thermally conductive material is easy to agglomerate, and the inorganic material is unevenly dispersed during the mixing process with the epoxy resin monomer, resulting in uneven dispersion of the inorganic thermally conductive material in the network matrix formed by cross-linking the epoxy resin monomer, which greatly limits the improvement of the thermal conductivity of the thermally conductive package; in addition, due to the poor interface bonding between the inorganic thermally conductive material and the epoxy resin monomer, the constructed thermally conductive network is not stable enough, and there is a large interface thermal barrier between the cross-linked network matrix formed by the epoxy resin monomer and the inorganic thermally conductive material, which greatly limits the improvement of the thermal conductivity of the thermally conductive package. Summary of the invention
[0005] The present application provides a material for preparing a thermally conductive package and a preparation method thereof, a thermally conductive package and a preparation method thereof, and an electronic device, which are intended to improve the thermal conductivity of an existing thermally conductive package.
[0006] In a first aspect, the present application provides a method for preparing a material for preparing a thermally conductive package, comprising:
[0007] In the presence of water, a first mixed system containing a silane coupling agent, a first organic solvent and an inorganic thermal conductive material after alkali etching is subjected to a first reaction at 30-60° C. to obtain an intermediate.
[0008] Under the protection of inert gas, a second mixed system containing the intermediate, the second organic solvent and the epoxy monomer is subjected to a second reaction at 65-100°C.
[0009] Among them, the silane coupling agent contains amino groups, the inorganic thermal conductive material after alkali etching contains hydroxyl groups, and the structural formula of the epoxy monomer is as follows:
[0010] Wherein, R is the carbon chain skeleton of the epoxy monomer.
[0011] In the preparation method of the material for preparing the thermally conductive package provided by the present application, the surface of the inorganic thermally conductive material after alkali etching has a large number of hydroxyl groups; at 30-60°C, the silanol bonds formed after the hydrolysis of the silane coupling agent can dehydrate and condense with the hydroxyl groups on the surface of the inorganic thermally conductive material, thereby stably connecting the silane coupling agent and the inorganic thermally conductive material together. Since the silane coupling agent contains an amino group, at 65-100°C and under the protection of inert gas conditions, the amino group on the silane coupling agent reacts with an epoxy group on the epoxy monomer, so that the silane coupling agent and the epoxy monomer are stably connected together, thereby obtaining an overall material containing the inorganic thermally conductive material and the epoxy monomer connected together by the silane coupling agent (i.e., the material for preparing the thermally conductive package).
[0012] In the formed material for preparing the thermally conductive package, the remaining epoxy groups on the epoxy monomer can undergo a ring-opening cross-linking reaction in the presence of a curing agent, thereby forming a thermally conductive package; due to the covalent connection between the inorganic thermally conductive material and the epoxy resin monomer, the inorganic thermally conductive material in the thermally conductive package can be evenly distributed in the network system matrix formed by the cross-linking of the epoxy monomer, so that the constructed thermal network is relatively stable, which is beneficial to avoid the poor thermal conductivity of the thermally conductive package caused by "poor interface bonding between the inorganic thermally conductive material and the cross-linked network matrix formed by the epoxy resin monomer" and "uneven dispersion of the inorganic thermally conductive material in the cross-linked network matrix formed by the epoxy monomer", which is beneficial to improve the thermal conductivity of the thermally conductive package.
[0013] In combination with the first aspect, in an optional embodiment of the present application, the molar ratio of the silane coupling agent to the inorganic thermal conductive material is (3-10):1; the molar ratio of the silane coupling agent to the epoxy monomer is (25-40):1.
[0014] Under the above ratio conditions, it is beneficial to increase the ratio and reaction speed of the silane coupling agent connecting the inorganic thermal conductive material and the epoxy monomer.
[0015] Optionally, the inorganic thermally conductive material includes at least one of boron nitride and silicon carbide.
[0016] Optionally, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0017] In combination with the first aspect, in an optional embodiment of the present application, the first mixing system further contains a promoter, and the promoter includes at least one of ammonia water, ethanolamine and triethanolamine.
[0018] The above technical solution is beneficial to increasing the proportion and reaction speed of the silane coupling agent connecting the inorganic thermal conductive material.
[0019] Optionally, the molar ratio of the accelerator to the silane coupling agent is (3-5):1.
[0020] In combination with the first aspect, in an optional implementation manner of the present application, the alkaline etching step includes: mixing the inorganic thermal conductive material with a strong alkaline solution at 60-100° C.; the molar concentration of the strong alkaline solution is 0.3-0.7M.
[0021] The above technical solution can increase the number of hydroxyl groups on the surface of the inorganic thermally conductive material after alkali etching, thereby facilitating increasing the proportion of the silane coupling agent connecting the inorganic thermally conductive material.
[0022] In combination with the first aspect, in an optional embodiment of the present application, the structural formula of the epoxy monomer is as follows:
[0023]
[0024] And / or, the structural formula of the epoxy monomer is as follows:
[0025]
[0026] The use of the epoxy monomer with the above structure is beneficial to further improve the thermal conductivity of the formed thermally conductive package.
[0027] Optionally, the epoxy monomer is an epoxy monomer treated with a magnetic field of 5-15T.
[0028] In a second aspect, the present application provides a material for preparing a thermally conductive package. The material for preparing a thermally conductive package is prepared by the method for preparing a material for preparing a thermally conductive package provided in the first aspect.
[0029] Since the material provided in the present application for preparing the thermally conductive package is an integral material containing an inorganic thermally conductive material and an epoxy monomer connected together by a silane coupling agent, the remaining epoxy groups on the epoxy monomer in the material can undergo a ring-opening cross-linking reaction in the presence of a curing agent, thereby forming a thermally conductive package; since the inorganic thermally conductive material and the epoxy resin monomer are covalently connected, the constructed thermally conductive network is relatively stable, and the inorganic thermally conductive material in the thermally conductive package can be evenly distributed in the network matrix formed by cross-linking the epoxy monomer, which is beneficial to avoid the poor thermal conductivity of the thermally conductive package caused by "poor interface bonding between the inorganic thermally conductive material and the cross-linked network matrix formed by the epoxy resin monomer" and "uneven dispersion of the inorganic thermally conductive material in the cross-linked network matrix formed by the epoxy monomer", thereby helping to improve the thermal conductivity of the thermally conductive package.
[0030] In a third aspect, the present application provides a method for preparing a thermally conductive package, comprising: subjecting a curing agent and the material for preparing the thermally conductive package provided in the second aspect to a cross-linking curing reaction at a temperature of 150-200°C.
[0031] The remaining epoxy groups on the epoxy monomer in the material used to prepare the thermally conductive package can undergo a ring-opening cross-linking reaction in the presence of a curing agent and at a temperature of 150-200°C, thereby forming a thermally conductive package; in the thermally conductive package, due to the covalent connection between the inorganic thermally conductive material and the epoxy resin monomer, the inorganic thermally conductive material is evenly distributed in the network matrix formed by the cross-linking of the epoxy monomer, so that the constructed thermally conductive network is relatively stable, which is conducive to avoiding the poor thermal conductivity of the thermally conductive package caused by "poor interface bonding between the inorganic thermally conductive material and the cross-linked network matrix formed by the epoxy resin monomer" and "uneven dispersion of the inorganic thermally conductive material in the cross-linked network matrix formed by the epoxy monomer", which is conducive to improving the thermal conductivity of the thermally conductive package.
[0032] In combination with the third aspect, in an optional embodiment of the present application, the cross-linking and curing reaction includes: firstly subjecting the curing agent and the material for preparing the thermally conductive package to a first cross-linking reaction at a temperature of 150-170°C, and then subjecting the curing agent and the material for preparing the thermally conductive package to a second cross-linking reaction at a temperature of 180-200°C.
[0033] The above technical solution, due to the step-by-step temperature rise cross-linking and curing method, can improve the cross-linking degree of the material used to prepare the thermally conductive package, thereby facilitating the improvement of the thermal conductivity and mechanical strength of the thermally conductive package.
[0034] Optionally, the first cross-linking reaction time is 1.5-2.5 hours, and the second cross-linking reaction time is 0.5-1.5 hours.
[0035] In a fourth aspect, the present application provides a thermally conductive package, which is manufactured using the method for manufacturing a thermally conductive package provided in the third aspect.
[0036] The thermally conductive package provided in the present application has good thermal conductivity, which greatly expands the application scope of the thermally conductive package.
[0037] In a fifth aspect, the present application provides an electronic device, comprising: a housing, components and a thermally conductive package as provided in the fourth aspect above; the components and the thermally conductive package are both arranged in the housing, and the thermally conductive package fills the gap between the housing and the components.
[0038] The electronic device provided in the present application uses the thermally conductive package provided in the present application, so that the components in the electronic device can be effectively and quickly cooled, which is beneficial to ensuring the normal operation of the electronic device. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 A flow chart of the preparation process of the material for preparing the thermally conductive package provided in this application. DETAILED DESCRIPTION
[0041] Figure 1 For the process flow chart of the material for preparing the thermally conductive package provided in this application, please refer to Figure 1 , the material for preparing the thermally conductive package comprises the following steps:
[0042] S10, in the presence of water, subjecting a first mixed system containing a silane coupling agent, a first organic solvent and an inorganic thermally conductive material after alkali etching to a first reaction at 30-60° C. to obtain an intermediate.
[0043] In the present application, the silane coupling agent contains amino groups, and the inorganic thermal conductive material after alkali etching contains hydroxyl groups.
[0044] The surface of the inorganic thermal conductive material after alkali etching has a large number of hydroxyl groups; in the presence of water, the silane coupling agent can undergo a hydrolysis reaction to form a silanol bond; at 30-60°C, the silanol bond formed after the hydrolysis of the silane coupling agent can dehydrate and condense with the hydroxyl groups on the surface of the inorganic thermal conductive material, thereby stably connecting the silane coupling agent and the inorganic thermal conductive material together.
[0045] As an example, the temperature of the first reaction may be any one of 30°C, 40°C, 45°C, 50°C, 55°C or 60°C, or a range between any two of them.
[0046] In some optional embodiments, the first reaction time may be 4-8 hours.
[0047] As an example, the time of the first reaction can be any one of 4 h, 4.5 h, 5 h, 6 h, 7 h and 8 h, or a range between any two of them.
[0048] In some optional embodiments, the molar ratio of the silane coupling agent to the inorganic thermal conductive material is (3-10): 1. Under the above ratio conditions, it is beneficial to increase the ratio and reaction rate of the silane coupling agent connecting the inorganic thermal conductive material.
[0049] As an example, the molar ratio of the silane coupling agent to the inorganic thermal conductive material may be any one of 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, or a range between any two of them.
[0050] As an example, the inorganic thermally conductive material includes at least one of boron nitride, silicon carbide, aluminum oxide, and silicon dioxide.
[0051] Furthermore, the inorganic thermally conductive material includes at least one of boron nitride and silicon carbide, which is beneficial to further improve the thermal conductivity of the material used to prepare the thermally conductive package.
[0052] As an example, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0053] Illustratively, the first organic solvent includes at least one of toluene and xylene.
[0054] In some optional embodiments, the first mixed system further contains a promoter, which includes at least one of ammonia, ethanolamine and triethanolamine. The use of the promoter is conducive to increasing the proportion and reaction rate of the silane coupling agent connecting the inorganic thermal conductive material.
[0055] Furthermore, the accelerator is ammonia water, which can further increase the proportion and reaction rate of the silane coupling agent connecting the inorganic thermal conductive material. Furthermore, the molar ratio of the accelerator to the silane coupling agent is (3-5):1, which can further increase the proportion and reaction rate of the silane coupling agent connecting the inorganic thermal conductive material.
[0056] As an example, the molar ratio of the accelerator to the silane coupling agent can be any one of 3:1, 3.2:1, 3.5:1, 3.7:1, 4:1, 4.2:1, 4.5:1 or 5:1, or a range between any two of them.
[0057] In some optional embodiments, the alkali etching step includes: mixing the inorganic thermal conductive material with a strong alkali solution at 60-100° C.; the molar concentration of the strong alkali solution is 0.3-0.7 M. The above technical solution can increase the number of hydroxyl groups on the surface of the inorganic thermal conductive material after alkali etching, thereby facilitating an increase in the proportion of the silane coupling agent connecting the inorganic thermal conductive material.
[0058] As an example, the temperature of the mixed treatment in the alkali etching step can be any one of 60°C, 70°C, 75°C, 80°C, 85°C, 90°C or 100°C or a range between any two of them. The molar concentration of the strong alkali solution can be any one of 0.3M, 0.35M, 0.4M, 0.5M, 0.55M, 0.6M and 0.7M or a range between any two of them. The strong alkali can be sodium hydroxide or potassium hydroxide, etc. The time of the mixed treatment in the alkali etching step can be 10-14h.
[0059] Furthermore, the alkali etching step includes: mixing the inorganic thermal conductive material with the strong alkali solution, performing ultrasonic treatment; and then stirring and mixing at 60-100°C.
[0060] As an example, the power of ultrasonic treatment is 200-350W, the time of ultrasonic treatment is 15-30min, and the time of stirring and mixing is 10-14h.
[0061] S20, under the protection of an inert gas, subjecting a second mixed system containing the intermediate, a second organic solvent and an epoxy monomer to a second reaction at 65-100° C.
[0062] In this application, the structural formula of the epoxy monomer is as follows:
[0063] Wherein, R is the carbon chain skeleton of the epoxy monomer.
[0064] Since the silane coupling agent contains an amino group, under the protection of inert gas at 65-100°C, the two active hydrogens in the amino group on the intermediate silane coupling agent can react with an epoxy group on the epoxy monomer, so that the silane coupling agent and the epoxy monomer are stably connected together, thereby obtaining an overall material containing an inorganic thermal conductive material and an epoxy monomer connected together by the silane coupling agent (i.e., a material for preparing a thermally conductive package). In addition, inert gas protection is conducive to ensuring the effective conduction of the second reaction, and thus is conducive to ensuring the connection ratio of the silane coupling agent and the epoxy monomer.
[0065] In the material for preparing a thermally conductive package formed by the above method, the remaining epoxy groups on the epoxy monomer can undergo a ring-opening cross-linking reaction in the presence of a curing agent to form a thermally conductive package; due to the covalent connection between the inorganic thermally conductive material and the epoxy resin monomer, the inorganic thermally conductive material in the thermally conductive package can be evenly distributed in the network system matrix formed by the cross-linking of the epoxy monomer, so that the constructed thermally conductive network is relatively stable, which is beneficial to avoid the poor thermal conductivity of the thermally conductive package caused by "poor interface bonding between the inorganic thermally conductive material and the cross-linked network matrix formed by the epoxy resin monomer" and "uneven dispersion of the inorganic thermally conductive material in the cross-linked network matrix formed by the epoxy monomer", which is beneficial to improve the thermal conductivity of the thermally conductive package.
[0066] As an example, the temperature of the second reaction can be any one of 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 100°C, or a range between any two of them.
[0067] It should be noted that the present application does not limit the structure of the carbon chain skeleton in the epoxy monomer.
[0068] In some optional embodiments, the second reaction time may be 10-14 hours.
[0069] In some optional embodiments, the molar ratio of the silane coupling agent to the epoxy monomer is (25-40):1, which is beneficial to increase the ratio of the silane coupling agent to the epoxy monomer and the reaction rate.
[0070] As an example, the molar ratio of the silane coupling agent to the epoxy monomer may be any one of 25:1, 27:1, 30:1, 32:1, 35:1, 37:1, 39:1 or 40:1, or a range between any two of them.
[0071] In some optional embodiments, the structural formula of the epoxy monomer is as follows:
[0072]
[0073] And / or, the structural formula of the epoxy monomer is as follows:
[0074]
[0075] The use of the epoxy monomer with the above structure is beneficial to further improve the thermal conductivity of the formed thermally conductive package.
[0076] Furthermore, the epoxy monomer used in the second reaction is: the epoxy monomer of the above structure is treated with a magnetic field of 5-15 T. After the magnetic field treatment of 5-15 T, the crystallinity of the cross-linked network matrix formed by the epoxy monomer and the orderliness of the molecular segments in the cross-linked network matrix can be improved, which is beneficial to improving the transmission speed of phonons in the cross-linked network matrix, and further beneficial to improving the thermal conductivity of the thermally conductive package.
[0077] As an example, the condition of the magnetic field treatment may be any one of 5T, 7T, 10T, 12T and 15T, or a range of values between any two of them.
[0078] In some optional embodiments, the intermediate used in the second reaction is a substance obtained by drying after the first reaction. As an example, the drying step includes: filtering and washing the system after the first reaction with anhydrous ethanol for multiple times, and then drying at 50-70°C.
[0079] It should be noted that, in other feasible implementations, the system after the first reaction may also be used directly as an intermediate to further undergo a second reaction with a second organic solvent and an epoxy monomer.
[0080] In some optional embodiments, the system after the second reaction is washed and filtered multiple times with anhydrous ethanol and dimethyl sulfoxide, and then dried at 60-90° C. The present application also provides a material for preparing a thermally conductive package, and the material for preparing a thermally conductive package is prepared by the preparation method of the material for preparing a thermally conductive package as provided above.
[0081] Since the material provided in the present application for preparing the thermally conductive package is an integral material containing an inorganic thermally conductive material and an epoxy monomer connected together by a silane coupling agent, the remaining epoxy groups on the epoxy monomer in the material can undergo a ring-opening cross-linking reaction in the presence of a curing agent, thereby forming a thermally conductive package; since the inorganic thermally conductive material and the epoxy resin monomer are covalently connected, the constructed thermally conductive network is relatively stable, and the inorganic thermally conductive material in the thermally conductive package can be evenly distributed in the network matrix formed by cross-linking the epoxy monomer, which is beneficial to avoid the poor thermal conductivity of the thermally conductive package caused by "poor interface bonding between the inorganic thermally conductive material and the cross-linked network matrix formed by the epoxy resin monomer" and "uneven dispersion of the inorganic thermally conductive material in the cross-linked network matrix formed by the epoxy monomer", thereby helping to improve the thermal conductivity of the thermally conductive package.
[0082] The present application also provides a method for preparing a thermally conductive package, comprising: subjecting a curing agent and the above-mentioned material for preparing the thermally conductive package to a cross-linking curing reaction at a temperature of 150-200°C.
[0083] The remaining epoxy groups on the epoxy monomer in the material used to prepare the thermally conductive package can undergo a ring-opening cross-linking reaction in the presence of a curing agent and at a temperature of 150-200°C, thereby forming a thermally conductive package; in the thermally conductive package, due to the covalent connection between the inorganic thermally conductive material and the epoxy resin monomer, the inorganic thermally conductive material is evenly distributed in the network matrix formed by the cross-linking of the epoxy monomer, so that the constructed thermally conductive network is relatively stable, which is conducive to avoiding the poor thermal conductivity of the thermally conductive package caused by "poor interface bonding between the inorganic thermally conductive material and the cross-linked network matrix formed by the epoxy resin monomer" and "uneven dispersion of the inorganic thermally conductive material in the cross-linked network matrix formed by the epoxy monomer", which is conducive to improving the thermal conductivity of the thermally conductive package.
[0084] As an example, the temperature of the cross-linking curing reaction may be any one of 150° C., 160° C., 170° C., 175° C., 180° C., 190° C. and 200° C., or a range between any two of them.
[0085] Furthermore, the cross-linking curing reaction includes: firstly subjecting the curing agent and the material for preparing the thermally conductive package to a first cross-linking reaction at a temperature of 150-170° C., and then subjecting the curing agent and the material for preparing the thermally conductive package to a second cross-linking reaction at a temperature of 180-200° C. Since the step-wise temperature-raising cross-linking curing method is adopted, the cross-linking degree of the material for preparing the thermally conductive package can be increased, thereby facilitating the improvement of the thermal conductivity and mechanical strength of the thermally conductive package.
[0086] As an example, the temperature of the first cross-linking reaction can be any one of 150°C, 155°C, 160°C, 165°C and 170°C, or a range between any two of them; the temperature of the second cross-linking reaction can be any one of 180°C, 185°C, 190°C, 195°C and 200°C, or a range between any two of them.
[0087] Furthermore, the first cross-linking reaction time is 1.5-2.5 hours, and the second cross-linking reaction time is 0.5-1.5 hours.
[0088] As an example, the time for the first cross-linking reaction can be any one of 1.5h, 1.75h, 2.0h, 2.2h and 2.5h, or a range between any two of them; the time for the second cross-linking reaction can be any one of 0.5h, 0.75h, 1.0h, 1.2h and 1.5h, or a range between any two of them.
[0089] As an example, the curing agent includes at least one of 4,4'-diaminophenylsulfone, 4,4'-ethylenediphenylamine, 4,4'-diaminodiphenylmethane, and benzidine.
[0090] In some optional embodiments, the method for preparing the thermally conductive package further comprises: before the cross-linking curing reaction, adding deionized water to the third mixed system containing the curing agent, the material for preparing the thermally conductive package, and the dispersing solvent, removing the liquid phase to obtain a precipitate; and drying the precipitate. The above technical solution can make the system for the cross-linking curing reaction relatively pure, which is conducive to better cross-linking curing reaction and is conducive to avoiding the influence of the cross-linking degree of the cross-linking reaction due to the presence of impurities.
[0091] The present application also provides a thermally conductive package, which is manufactured using the thermally conductive package manufacturing method as described above.
[0092] The thermally conductive package provided in the present application has good thermal conductivity, which greatly expands the application scope of the thermally conductive package.
[0093] The present application provides an electronic device, which includes: a housing, components and a thermally conductive package as provided above; the components and the thermally conductive package are both arranged in the housing, and the thermally conductive package fills the gap between the housing and the components.
[0094] The electronic device provided in the present application uses the thermally conductive package provided in the present application, so that the components in the electronic device can be effectively and quickly cooled, which is beneficial to ensuring the normal operation of the electronic device.
[0095] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0096] Example 1
[0097] This embodiment provides a thermally conductive package, which includes the following steps:
[0098] (1) 1.6 g of nano-SiC material was added to 100 mL of 0.5 mol / L NaOH solution, and ultrasonicated at 300 W for 20 min to obtain a uniform dispersion system; the dispersion system was transferred to a three-necked flask, magnetically stirred at 80 ° C, and condensed and refluxed for 12 h; cooled to room temperature, washed with deionized water for multiple times and filtered until neutral, and placed in an oven at 80 ° C to obtain a surface alkali-washed and etched modified nano-SiC material.
[0099] (2) The modified nano-silicon carbide material obtained in step (1) was added to 60 mL of toluene, and ultrasonicated at 300 W for 10 min until uniformly dispersed, and then transferred to a three-necked flask, 84 g of 25 wt% ammonia water and 44.2 g of γ-aminopropyltriethoxysilane were added, and magnetic stirring was performed at 50° C., and condensation reflux reaction was performed for 6 h; cooled to room temperature, filtered and washed with anhydrous ethanol several times, and dried in an oven at 60° C. to obtain an intermediate.
[0100] (3) The intermediate obtained in step (2) and 2.28 g of epoxy monomer are added to 30 mL of dimethyl sulfoxide, and ultrasonicated at 300 W for 30 min to obtain a uniform dispersion; the dispersion is transferred to a 500 mL three-necked flask, and reacted at 80 ° C with magnetic stirring and condensation reflux under nitrogen protection for 12 h; after cooling to room temperature, the mixture is washed and filtered with dimethyl sulfoxide and anhydrous ethanol for multiple times, and dried at 80 ° C to obtain a material for preparing a thermally conductive package.
[0101] The epoxy monomer is an epoxy monomer treated with a magnetic field of 10 T, and the structural formula of the epoxy monomer is as follows:
[0102]
[0103] (4) 3.4 g of the material for preparing the thermally conductive package obtained in step (3) and 0.54 g of 4,4'-diaminophenylsulfone were uniformly mixed in 10 mL of dimethyl sulfoxide to form a dispersion; 200 mL of deionized water was added to the dispersion, and the liquid phase was removed to obtain a precipitate; the precipitate was dried in an oven at 80°C for 1 h; the dried material was cross-linked and cured at 170°C for 2 h, and then the temperature was raised to 180°C and cross-linked and cured for another 1 h to obtain a thermally conductive package.
[0104] Example 2
[0105] (1) 0.16 g of nano-silicon carbide material was added to 100 mL of 0.3 mol / L NaOH solution, and ultrasonicated at 200 W for 30 min to obtain a uniform dispersion system; the dispersion system was transferred to a three-necked flask, magnetically stirred at 60 ° C, and condensed and refluxed for 14 h; cooled to room temperature, washed with deionized water for multiple times and filtered until neutral, and placed in an oven at 80 ° C to obtain a modified nano-silicon carbide material with surface alkali washing and etching.
[0106] (2) The modified nano-silicon carbide material obtained in step (1) was added to 60 mL of toluene, ultrasonicated at 300 W for 10 min until uniformly dispersed, and then transferred to a three-necked flask, 67.2 g of 25 wt% ammonia water and 26.52 g of γ-aminopropyltriethoxysilane coupling agent were added, and magnetic stirring was performed at 30° C., and condensation reflux reaction was performed for 8 h; cooled to room temperature, filtered and washed with anhydrous ethanol several times, and dried in an oven at 50° C. to obtain an intermediate.
[0107] (3) The intermediate obtained in step (2) and 1.824 g of epoxy monomer are added to 30 mL of dimethyl sulfoxide, and ultrasonicated at 300 W for 30 min to obtain a uniform dispersion; the dispersion is transferred to a 500 mL three-necked flask, and reacted at 65 ° C with magnetic stirring and condensation reflux under nitrogen protection for 14 h; after cooling to room temperature, the mixture is washed and filtered with dimethyl sulfoxide and anhydrous ethanol for multiple times, and dried at 80 ° C to obtain a material for preparing a thermally conductive package.
[0108] The epoxy monomer is an epoxy monomer treated with a 5T magnetic field, and the structural formula of the epoxy monomer is as follows:
[0109]
[0110] (4) 3.4 g of the material for preparing a thermally conductive package obtained in step (3) and 0.54 g of 4,4'-diaminophenylsulfone were uniformly mixed in 10 mL of dimethyl sulfoxide to form a dispersion; 200 mL of deionized water was added to the dispersion, and the liquid phase was removed to obtain a precipitate; the precipitate was dried in an oven at 80° C. for 1 h; the dried material was cross-linked and cured at 150° C. for 2.5 h, and then the temperature was raised to 180° C. and cross-linked and cured for another 1.5 h to obtain a thermally conductive package.
[0111] Example 3
[0112] (1) 0.16 g of nano-silicon carbide material was added to 100 mL of 0.7 mol / L NaOH solution, and ultrasonicated at 350 W for 15 min to obtain a uniform dispersion system; the dispersion system was transferred to a three-necked flask, magnetically stirred at 100 ° C, and condensed and refluxed for 10 h; cooled to room temperature, washed with deionized water for multiple times and filtered until neutral, and placed in an oven at 80 ° C to obtain a surface alkali-washed and etched modified nano-silicon carbide material.
[0113] (2) The modified nano-silicon carbide material obtained in step (1) was added to 60 mL of toluene, ultrasonicated at 300 W for 10 min until uniformly dispersed, and then transferred to a three-necked flask, 280 g of 25 wt% ammonia water and 88.4 g of γ-aminopropyltriethoxysilane coupling agent were added, and magnetic stirring was performed at 60° C., and condensation reflux reaction was performed for 8 h; cooled to room temperature, filtered and washed with anhydrous ethanol several times, and dried in an oven at 70° C. to obtain an intermediate.
[0114] (3) The intermediate obtained in step (2) and 7.296 g of epoxy monomer are added to 30 mL of dimethyl sulfoxide, and ultrasonicated at 300 W for 30 min to obtain a uniform dispersion; the dispersion is transferred to a 500 mL three-necked flask, and magnetically stirred at 100 ° C. and condensed under reflux under nitrogen protection for 10 h; after cooling to room temperature, the mixture is washed and filtered with dimethyl sulfoxide and anhydrous ethanol for multiple times, and dried at 80 ° C. to obtain a material for preparing a thermally conductive package.
[0115] The epoxy monomer is an epoxy monomer treated with a magnetic field of 15 T, and the structural formula of the epoxy monomer is as follows:
[0116]
[0117] (4) 3.4 g of the material for preparing a thermally conductive package obtained in step (3) and 0.54 g of 4,4'-diaminophenylsulfone were uniformly mixed in 10 mL of dimethyl sulfoxide to form a dispersion; 200 mL of deionized water was added to the dispersion, and the liquid phase was removed to obtain a precipitate; the precipitate was dried in an oven at 80° C. for 1 h; the dried material was cross-linked and cured at 170° C. for 1.5 h, and then the temperature was raised to 200° C. and cross-linked and cured for another 0.5 h to obtain a thermally conductive package.
[0118] Example 4
[0119] This embodiment provides a thermally conductive package. The difference between this embodiment and Embodiment 1 is that 1.6 g of silicon carbide in Embodiment 1 is replaced by 1.6 g of boron nitride.
[0120] Example 5
[0121] This embodiment provides a thermally conductive package. The difference between this embodiment and Embodiment 1 is that 1.6 g of silicon carbide in Embodiment 1 is replaced by 1.6 g of silicon dioxide.
[0122] Example 6
[0123] This embodiment provides a thermally conductive package. The difference between this embodiment and Embodiment 1 is that 44.2 g of γ-aminopropyltriethoxysilane in Embodiment 1 is replaced with 35.8 g of γ-aminopropyltrimethoxysilane.
[0124] Example 7
[0125] This embodiment provides a thermally conductive package. The difference between this embodiment and embodiment 1 is that the structural formula of the epoxy monomer is as follows:
[0126]
[0127] The mass of epoxy monomer used is 2.14 g.
[0128] Example 8
[0129] This embodiment provides a thermally conductive package. The difference between this embodiment and Embodiment 1 is that the epoxy monomer has not been treated with a 15T magnetic field.
[0130] Example 9
[0131] This embodiment provides a thermally conductive package. The difference between this embodiment and Embodiment 1 is that 84 g of 25 wt % ammonia water is replaced with 146.4 g of 25 wt % ethanolamine.
[0132] Example 10
[0133] This embodiment provides a thermally conductive package. The difference between this embodiment and Embodiment 1 is that 84 g of 25 wt % ammonia water is replaced with 357.6 g of 25 wt % triethanolamine.
[0134] Embodiment 11
[0135] This embodiment provides a thermally conductive package. The difference between this embodiment and Embodiment 1 is that the treatment of the dried precipitate in step (4) is different.
[0136] In this embodiment, the dried material is cross-linked and cured at 200° C. for 2 hours to obtain a thermally conductive package.
[0137] Example 12
[0138] This embodiment provides a thermally conductive package. The difference between this embodiment and embodiment 1 is that step (4) is different. Step (4) of this embodiment is as follows:
[0139] 1 g of epoxy monomer (substance A) was dissolved in 10 mL of dimethyl sulfoxide to form a first dispersion; 2.88 g of the material for preparing the thermally conductive package obtained in step (3) and 0.61 g of 4,4'-diaminophenylsulfone were uniformly mixed in 10 mL of dimethyl sulfoxide to form a second dispersion; the first dispersion and the second dispersion were mixed, 200 mL of deionized water was added to the mixed system, and the liquid phase was removed to obtain a precipitate; the precipitate was dried in an oven at 80°C for 1 hour; the dried material was cross-linked and cured at 170°C for 2 hours, and then the temperature was raised to 180°C and cross-linked and cured for another 1 hour to obtain a thermally conductive package.
[0140] The epoxy monomer is an epoxy monomer treated with a magnetic field of 10 T, and the structural formula of the epoxy monomer is as follows:
[0141]
[0142] Comparative Example 1
[0143] This comparative example provides a thermally conductive package, which includes the following steps:
[0144] 2.28g of epoxy monomer, 1.6g of nano silicon carbide material and 0.61g of 4,4'-diaminophenylsulfone were uniformly mixed in 10mL of dimethyl sulfoxide to form a dispersion; 200mL of deionized water was added to the dispersion, and the liquid phase was removed to obtain a precipitate; the precipitate was dried in an oven at 80°C for 1h; the dried material was cross-linked and cured at 170°C for 2h, and then heated to 180°C and cross-linked and cured for another 1h to obtain a thermally conductive package. Among them, the epoxy monomer is an epoxy monomer treated with a 10T magnetic field, and the structural formula of the epoxy monomer is as follows:
[0145]
[0146] Comparative Example 2
[0147] This comparative example provides a thermally conductive package, which includes the following steps:
[0148] 2 g of epoxy monomer and 0.54 g of 4,4'-diaminophenylsulfone were uniformly mixed in 10 mL of dimethyl sulfoxide to form a dispersion; 200 mL of deionized water was added to the dispersion, and the liquid phase was removed to obtain a precipitate; the precipitate was dried in an oven at 80°C for 1 hour; the dried material was cross-linked and cured at 170°C for 2 hours, and then the temperature was raised to 180°C and cross-linked and cured for another 1 hour to obtain a thermally conductive package.
[0149] The epoxy monomer is an epoxy monomer treated with a magnetic field of 10 T, and the structural formula of the epoxy monomer is as follows:
[0150]
[0151] Experimental example
[0152] The thermal conductivity of the thermally conductive packages prepared in Examples 1-12 and Comparative Examples 1-2 was tested. The test results are shown in Table 1.
[0153] Table 1
[0154] Thermal conductivity (W / (m·K)) Thermal conductivity (W / (m·K)) Example 1 15.1 Example 8 13.4 Example 2 14.9 Example 9 14.5 Example 3 15.3 Example 10 14.3 Example 4 13.8 Embodiment 11 13.2 Example 5 10.1 Example 12 13.9 Example 6 15.2 Comparative Example 1 8.7 Example 7 15 Comparative Example 2 0.9
[0155] It can be seen from Table 1 that the thermal conductivity of the thermally conductive packages prepared in Examples 1-12 is higher than that of the thermally conductive packages prepared in Comparative Examples 1-2, indicating that compared with the "direct cross-linking and curing method of the system containing epoxy monomer and nano-silicon carbide (i.e., inorganic thermally conductive material) directly adopted in Comparative Example 1" and the "direct cross-linking and curing method of epoxy monomer directly adopted in Comparative Example 2", the method of "connecting the inorganic thermally conductive material and the epoxy monomer together through a silane coupling agent to form an integral material" adopted in Examples 1-12 can effectively improve the thermal conductivity of the thermally conductive packages prepared.
[0156] From the comparison between Example 1 and Examples 4-5, it can be seen that compared with using silicon dioxide as the inorganic thermal conductive material, using silicon carbide or boron nitride as the inorganic thermal conductive material can further improve the thermal conductivity of the manufactured thermally conductive package.
[0157] From the comparison between Example 1 and Example 6, it can be seen that the silane coupling agent is selected from γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane, both of which can achieve good thermal conductivity of the prepared thermally conductive package.
[0158] From the comparison between Example 1 and Example 7, it can be seen that the epoxy monomer selected from Example 1 or Example 7 can achieve good thermal conductivity of the thermally conductive package.
[0159] From the comparison between Example 1 and Examples 9-10, it can be seen that, compared with using triethanolamine or ethanolamine as the accelerator, using ammonia water as the accelerator can further improve the thermal conductivity of the prepared thermally conductive package.
[0160] From the comparison between Example 1 and Example 11, it can be seen that the cross-linking and curing method using the gradient temperature rise cross-linking and curing method can further improve the thermal conductivity of the prepared thermally conductive package.
[0161] From the comparison between Example 1 and Example 12, it can be seen that compared with the method of "mixing the epoxy monomer with the material for preparing the thermally conductive package and then cross-linking and curing" in Example 12, the method of "directly cross-linking and curing the prepared material for preparing the thermally conductive package" in Example 1 can further improve the thermal conductivity of the prepared thermally conductive package.
[0162] In summary, the thermal conductivity of the thermally conductive package can be effectively improved by cross-linking and curing the material for preparing the thermally conductive package provided in the present application to form the thermally conductive package.
[0163] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A method for preparing a material for preparing a thermally conductive package, characterized in that: include: In the presence of water, a first mixed system containing a silane coupling agent, a first organic solvent and an inorganic thermal conductive material after alkali etching is subjected to a first reaction at 30-60° C. to obtain an intermediate; Under the protection of inert gas, subjecting the second mixed system containing the intermediate, the second organic solvent and the epoxy monomer to a second reaction at 65-100° C.; Wherein, the silane coupling agent contains amino groups, the inorganic thermal conductive material after alkali etching contains hydroxyl groups, and the structural formula of the epoxy monomer is as follows: In the formula, R is the carbon chain skeleton of the epoxy monomer.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the silane coupling agent to the inorganic thermal conductive material is (3-10):1; the molar ratio of the silane coupling agent to the epoxy monomer is (25-40):1; Optionally, the inorganic thermally conductive material includes at least one of boron nitride and silicon carbide; Optionally, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
3. The preparation method according to claim 1, characterized in that: The first mixed system further contains a promoter, which includes at least one of ammonia, ethanolamine and triethanolamine; Optionally, the molar ratio of the accelerator to the silane coupling agent is (3-5):
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that The alkali etching step comprises: mixing the inorganic thermal conductive material with a strong alkali solution at 60-100° C.; the molar concentration of the strong alkali solution is 0.3-0.7M.
5. The preparation method according to any one of claims 1 to 3, characterized in that: The structural formula of the epoxy monomer is as follows: And / or, the structural formula of the epoxy monomer is as follows: Optionally, the epoxy monomer is an epoxy monomer treated with a magnetic field of 5-15T.
6. A material for preparing a thermally conductive package, characterized in that: The material for preparing a thermally conductive package is prepared by the method for preparing a material for preparing a thermally conductive package according to any one of claims 1 to 5.
7. A method for preparing a thermally conductive package, characterized in that: include: The curing agent and the material for preparing a thermally conductive package as claimed in claim 6 are subjected to a crosslinking and curing reaction at a temperature of 150-200°C.
8. The preparation method according to claim 7, characterized in that: The cross-linking curing reaction comprises: firstly subjecting the curing agent and the material for preparing the thermally conductive package to a first cross-linking reaction at a temperature of 150-170° C., and then subjecting the curing agent and the material for preparing the thermally conductive package to a second cross-linking reaction at a temperature of 180-200° C.; Optionally, the first cross-linking reaction time is 1.5-2.5 hours, and the second cross-linking reaction time is 0.5-1.5 hours.
9. A thermally conductive package, characterized in that: The thermally conductive package is manufactured by the method for manufacturing a thermally conductive package according to claim 7 or 8.
10. An electronic device, characterized in that: The electronic device comprises: a housing, components and the thermally conductive package as claimed in claim 9; The components and the heat-conducting package are both arranged in the housing, and the heat-conducting package fills the gap between the housing and the components.
Citation Information
Cited By
Paraphthalimide bis (4-amino-3-methylphenol) diglycidyl ether Schiff base single crystal and preparation method thereof
CN121135666A